The Implementation of Destroyed Land Status Determination and the Provision of Compassionate Funds for Communities Affected by the Barrage Project (A Case Study in Jeruksari Village, Pekalongan Regency) (Indonesian Journal of Agrarian Law, 2026)
Permanent tidal floods in Jeruksari Village, Pekalongan Regency, have eliminated the physical form and function of community-owned land. This necessitated a "destroyed land" status as an administrative prerequisite for land procurement for a barrage project. However, this policy triggered social conflicts, particularly residents rejecting the compassionate funds as compensation, deeming it excessively low and unjust. This research analyzes the implementation of the destroyed land status in Jeruksari Village and assesses the effectiveness of compassionate funds as legal protection for affected communities. Using an empirical-juridical method with a descriptive-qualitative approach, data was collected via field observations, literature reviews, and interviews with residents, village officials, and the Land Office. Results show that administratively, the procedure for determining destroyed land aligns with the ATR/BPN Ministerial Regulation Number 3 of 2024, despite technical constraints from a 3-meter seawater inundation. However, the provision of compassionate funds (IDR 29,500 per square meter) is ineffective. Based on legal effectiveness and protection theories, this amount fails to fulfill justice and economic utility for communities losing their livelihoods. Therefore, improved policy communication and an evaluation of the compassionate fund mechanism are required to better reflect justice and utility for the affected communities.